The Use of Straw String Media to Improve Pre-Writing Skills for Children With Intellectual Disability - Ahadianingsih, Monica Nur (JASSI ANAKKU, 2021)
The purpose of this study was to determine the use of straw string media to improve pre-writing skills for children with intellectual disabilities. The research method used is Classroom Action Research (CAR) using demonstration learning methods and assignments. The research subjects were three children with intellectual disabilities at the Special School. The results showed that students experienced an increase in pre-writing skills. This is proved by the average acquisition of students' pre-writing skills which increases in each cycle. The results of the post-test showed that the average score of the students increased by 43% compared to the results of the pre-test. The success of this method is due to the use of straw string media which helps students improve pre-writing skills. This study demonstrates that the use of straw string media can make it easier for students to improve pre-writing skills and also makes it easier for teachers to guide students, especially children with intellectual disabilities.